Analysis of Investment Economy of Electric Boilers with Thermal Storage in Source-Load Application Scenarios - Yanping XU; Haobo SHI; Xiaohui QIN; Mingxin ZHAO; Jie BAI; Baodi Ding (Zhongguo dianli)
Electric boilers with thermal storage are a kind of electric-thermal conversion equipment, and they can be applied on both the source side and the load side of a power system to improve the flexibility of the system. This paper was designed to analyze the investment economy of electric boilers with thermal storage. Specifically, it built operation constraint models for electric boilers with thermal storage in different scenarios on the basis of the different operation modes of electric boilers with thermal storage in source-load scenarios and analyzed the composition of the economic benefits and comprehensive social benefits of the investment entities in different modes. Then, time-series production simulation was performed to construct an optimization model for the economic benefits of the investment entities for electric boilers with thermal storage with the objective of maximizing the annual economic benefits. Finally, the investment economy of the investment entities for electric heating with thermal storage was analyzed and evaluated by the net present value method. A provincial power grid in the Three North Region of China was further analyzed as an example, and investment economy was calculated according to the Northeast Electric Power Auxiliary Service Market Operation Rules. The results show that the application modes all have obvious comprehensive social benefits. The investment mode of thermal power plants has the highest profitability. In contrast, the investment modes of wind farms and load-side independent entities are not economically sustainable and thus require the adjustment of the corresponding market operation strategies.